Evasion and Time Consistency in the Taxation of Capital Income - Robin W. Boadway; Michael Keen (Queen's University, Department of Economics, 1993)
Evasion and time inconsistency have been prominent concerns in recent discussions capital income taxation, both theoretical and applied. This paper establishes a link between them, suggesting a potentially useful role for evasion additional to those previously identified: by committing to relatively tax enforcement, the government may be able to alleviate the welfare loss implied by its inability to commit to the tax rate. The scope for this role proves strikingly wide: it is optimal for the government to facilitate the evasion of the capital income taxes that it chooses to impose whenever the time consistent tax rate exceeds that which would be optimal if the government could commit to it.
Keywords: H21; H26; H30; 330